Melioidotic septic arthritis: report of two cases - Kamal, Muhammmad; Abdul Rhani, Shaharuddin; Masri, Siti Norbaya (Pakistan Medical Association Rawalpindi Islamabad Branch, 2011)
Osteomyelitis caused by Burkholderia pseudomallei is an uncommon presentation of melioidosis. The clinical diagnosis of melioidosis is difficult as the signs and symptoms are non-specific and the duration of symptoms varies widely. We present two cases of melioidotic septic arthritis, one associated with tibial osteomyelitis and another involving the femur.